THE INFLUENCE OF MANAGERIAL COMPETENCIES, BUSINESS PARTNERSHIPS AND ENTREPRENEURIAL SPIRIT ON FUND MANAGEMENT AND THEIR IMPLICATIONS TOWARDS FINANCIAL PERFORMANCE - SIHABUDIN; DAROJATUL ROMLI, ASEP; WARTONO, PAWIT (International Journal of Psychosocial Rehabilitation, 2020)
This research emphasizes more on the field of management science, especially financial management. His study was directed at the analysis of managerial competencies, business partnerships and entrepreneurial spirit which had an impact on fund management and its implementation on the financial performance of BUMDes in West Java which were certified in the Ministry of Village, Development of Disadvantaged Regions and Transmigration. Research is limited to company managers or management with the classification of BUMDes. The BUMDes studied were in regency areas in West Java, the determination of the location of the study was based on the establishment of West Java as a pilot area of the Joint Village Owned Enterprise (BUMDesa) and Desa'Smart by the Ministry of Village, Disadvantaged Regions and Transmigration (Ministry of PDTT) on the 29th August 2016. The results of the descriptive study show the Entrepreneurship Soul (X3) is lower than the other independent variables. While the average score for the Management Capability variable (Y) is higher than the other variables. And the Financial Performance variable (Z) is lower than the other variables. While the results of path analysis show Managerial Competence (X1) gives the most dominant contribution of 34.26%, the second largest influence is the Business Partnership Variable (X2) with a total influence of 33.08%. and Entrepreneurship Soul Variable (X3) made the weakest contribution of 7.68%. Calculation results The coefficient of determination (R squared) expressed in percentages illustrates the contribution of all independent variables by 75.01%. While other factors that are not examined and influence Management Capability are indicated by PyЄ1 = 0.250 or 25%. While the total management influence on financial performance is 84.4% and other factors that are not examined and influence financial performance are shown by PyЄ2 = 0.156